Defining a nation : India on the eve of independence, 1791 [id est 1945] - Embree, Ainslie Thomas; Carnes, Mark C. (Mark Christopher), 1950-; Embree, Ainslie Thomas (New York : Pearson Longman, 2005)
Aims to reconcile religious identity with nation building. This work consists of a game in which students are assigned roles, informed by classic texts, set in a particular moment of intellectual and social ferment. The game is set at Simla, where the British viceroy has invited leaders of religious and political constituencies
The Train to Simla. Introduction and Historical Context. Basic Materials and Maps.Map A: India 1945: Major Cities, Rivers and Princely States.Map B: Muslims as Percent of Total Population of India, 1931.The Historical Moment: June 1945. Special Rules: Departures from the Historical Context.Omission of Lord Wavell.Inclusion of The Nizam Of Hyderabad And, In Some Games, The Maharaja Of Kashmir.Inclusion of Hindu Mahasabha.Inclusion of Communist Party Leadership.Inclusion of Indeterminates.Duration of The Simla Conference.Roles.Possible Role Distribution.British Governor(S) General.Members of the Indian National Congress-The "Congress" Party.Representatives of the Muslim League.Adherents of Mohandas Gandhi.The Nizam of Hyderabad, A Muslim Prince.The Maharaja of Kashmir.Representative of the Sikhs.Dr. B. R. Ambedkar, Untouchable Leader.Representative of the Hindu Mahasabha.Leader of the Communist Party Of India.Various Indeterminates.Follower of Badshah Khan (Pashtun, North West Frontier Province).Basic Game Rules.Victory Objectives.Tactics and Weapons.Non-Violent Protests and "Direct Action."Civil War.Likely Electoral Strength.Special Note.Further Note: Electoral Simplicity.Fundamental Considerations.Schedule of Classes. Reading Assignments:Basic Sources.Quiz: Fourth Class.Sources Of The Indian Tradition, Vol. 2.Sample Quiz Questions: From India's Search For National Identity (Embree).Sample Quiz Questions: From Sources of Indian Tradition, Vol Ii.Written Assignments. IndiaChronology.Population.Basic Chronology.Historical Vocabulary: Essential Events.1757: British East India Company Defeats Mughals.1857: Sepoy Mutiny, or "The First War Of Indian Independence."1858: Government of India Act: British Direct Rule of India Commences.1885: Inc (Congress) Founded.Tilak: Hindu Revival.Militant Muslim.1905: Partition of Bengal.1906: Muslim League Founded.World War I.1919: Gandhi Arrives In India; The Amritsar Massacre.1919-1924: Khilafat Movement.1922: Gandhi Halts Nationwide Civil Disobedience.1930: Gandhi Salt March, Beginning Of Second Civil Disobedience Campaign.1935: Government of India Act.1937 Provincial Elections: Congress Wins.1940: Jinnah Calls For Muslim State.Vocabulary Words. Appendix A: Major Documents.Mahatma Gandhi's Statement on Satyagraha, 1 November 1919.On Hindu/Muslim Relations.Muslim Resolutions at Dacca, 30 December 1906.M. A. Jinnah: Presidential Address, Patna Session of the Muslim League, December 1938.Jinnah: Speech Before Assembly of Muslim League, Lahore, 1940.Gandhi: Extracts from The Collected Works .Nehru: Against Pakistan.Maulana Azad: Against Pakistan.V.D. Savarkar's Presidential Address at the 20th Session of the All-India Hindu Mahasabha, 1938.Gandhi: On Assam & Grouping Proposal.On The Untouchables.B. R. Ambedkar on the Depressed Classes, 1 January 1931, at the Indian Round Table Conference.Exerpts from Gandhi and Gandhism by B.R. Ambedkar.On The Future Of The Indian Economy.Jawaharlal Nehru's Presidential Address at the Lucknow Session of the National Congress, 12 April 1936 (Pro Socialism).Report on the Wardha Education Scheme, 1939 [Gandhi, inspired].The Communist Party of India.The Hindu Mahasabha's Economic Plan, 1931.Appendix B: Embree, India's Search for National Identity. Preface to the Revised Edition. Introduction. 1. One Great Nation?.Origins of Indian Nationalism.Profile: 1880s.2. Voices of India.First Responses to the West.Role of Regional Languages.Nationalist Organizations.Ilbert Bill.B.C. Tilak.Muslim Movements.3. Search for a Center.Curzon Era.New Radicalism.Muslim League.Constitutional Reforms.Revival of Nationalist Activity.4. The Emergence of Gandhi.Reactions to the Rowlatt Acts .Khilafat Movement.Non-Cooperation Movement.Non-Cooperation Begins.Civil Disobedience.Gandhi's Arrest.5. The Politics of Right Mistakes.India's International Status.Division in Nationalist Movement.First Demand for Independence.Hindu-Muslim Relations.Renewal of Nationalist Activity.1935 India Act .New Strength of the Muslim League.6. End and Beginning.Bargaining for Independence.Two-Nation Concept.Allied Pressure.Cripps mission."Quit India" Resolution.Negotiations for Independence.Partition.Appendix C: Recommended Reading.General Studies.Specialized Studies.Biographical Studies.
Includes the revised edition of India's search for national identity.
Includes bibliographical references (pages 182-184).
Keywords: Nationalism -- India -- Problems, exercises, etc; India -- Politics and government -- 1765-1947 -- Problems, exercises, etc; India -- History -- 20th century -- Sources